The new Fundeb and the fundamental right to education - Motta, Fabrício (Universidad Nacional del Litoral, 2019)
This work aims to analyze the ontological relationship between the right to education and the human dignity principle, in order to demonstrate that the new Fund for the Maintenance and Development of Basic Education (Fundeb) constitutes an instrument of concretization of the essential elements for a dignified life. With analytical and deductive methods, a research is made over the theoretical framework applicable to fundamental rights, the right to education, the human dignity principle and the Fundeb, supported by the norms of the respective provisions. The present study demonstrates the indispensability of the new Fundeb for the maintenance and development of education in Brazil, signaling risks inherent to eventual setbacks for this fundamental right.